Where is the Backward Peasant? Regional Crop Yields on Common and Private Land in Russia 1883-1913 - Michael Kopsidis; Katja Bruisch; Daniel W. Bromley (European Historical Economics Society (EHES), 2013)
This paper deals with agricultural dynamics in late-Imperial Russia. Based upon a comprehensive micro-level data set on annual yields between 1883 and 1913, we provide insight into regional differences of agricultural growth and the development prospects of Russian agriculture before WWI. Making use of the fact that— unique in Europe— contemporary Russian statistics distinguished between "privately owned" and mostly communally governed "peasant" land, we are able to test the implications of different landtenure systems for agricultural growth. In a broader sense we will challenge the stereotype of the "backward" peasant and the common narrative of Russia as an exception to the pan-European picture of economic development during the era of industrialization.
Keywords: N53; O13; Q15; 330; Russia; land productivity; peasant communal agriculture; land tenure